A mobile ad-hoc strategy to enhance ICT based education in Zimbabwean rural schools - Tsimba, Gerald; Mugoniwa, Beauty; Mutembedza, Amanda Nyasha (Institute of Electrical and Electronics Engineers Inc., 2021)
The following topics are dealt with: Internet; educational institutions; mobile computing; decision making; computer aided instruction; health care; educational courses; medical information systems; learning (artificial intelligence); further education.